Analysis of the Influence of Tether–Soil Interaction on the Attachment Trajectory of Small Celestial Body Detector - Yuyan Pei; Yu Yang; Guoning Wei; Yanchen Li; Hao Tian; Yang Zhao (Aerospace, 2025)
Multi-tethered spacecraft formation refers to a group of spacecraft that are connected by tethers. These spacecraft work together to perform tasks, such as encircling and capturing small celestial bodies. When the multi-tethered spacecraft formation is in the process of encircling and capturing small celestial bodies, there is a significant risk of the tethers colliding with the soil (or surface material) of the small celestial body. Such a collision can affect the trajectory of the small celestial body detector. To address this issue, a coupled dynamic model has been proposed. This model takes the interaction between the tethers and the soil of the small celestial body into account. The discrete element method is used to establish the asteroid soil model, and the multi-body-tethered spacecraft system is simplified into a two-spacecraft system. The detector model is established by using the dual quaternion, and the tether model is established by using the chain rod model combined with the finite element method. Finally, a multi-condition simulation test is carried out. The results show that the influence of tether–soil coupling on the trajectory of the detector is mainly as follows: the influence of tether–soil interaction on the trajectory of the detector is mainly reflected in the displacement of the detector along the axial direction of the tether.